Improvement of Spatial Quality in Area of Pilgrimage Tourism in Satui Barat Village, Tanah Bumbu Regency - Ina Revayanti; Sajidin Mukhlis Gunawan (Green Publisher Indonesia, 2024)
The development of tourism areas is closely related to improving the spatial quality of an area, but what happens if the tourism area is in a densely populated residential area with various characteristics of slums. Infrastructure, facilities and supporting utilities are not only built for the tourism area but also efforts to develop the local residential area so that it is in line with the image of improving the spatial quality of the tourism area. West Satui Village has a pilgrimage tourism area Makom Jati Keramat which is located in a residential area. With the approach and method of qualitative and quantitative analysis, improving the spatial quality of the tourism area can produce concepts and strategies for handling residential areas and developing pilgrimage tourism areas in West Satui Village, Satui District, Tanah Bumbu Regency.